Ancillary Liquidations and Pari Passu Distribution in a Winding up by the Court - THAM, Chee Ho (Institutional Knowledge at Singapore Management University, 2009)
The doctrine of ancillary liquidations stands at a crossroads. In Re HIH Casualty and General Insurance, the House of Lords stood evenly divided over whether that doctrine might be applied to permit the court to direct English liquidators in an ancillary liquidation to remit assets to foreign liquidators conducting the principal liquidation, even where such remission would result in an ultimate distribution of assets to unsecured creditors at variance with what such creditors would have received had the distribution been conducted by an English liquidator pursuant to English conceptions of pari passu distribution. This paper suggests that the insolvency legislation, closely read, reveals more support for application of ancillary liquidation doctrine in these circumstances so as to permit remission of assets than might initially be assumed.